1998
DOI: 10.1542/peds.101.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Children Who Prosper in Unfavorable Environments: The Relationship to Social Capital

Abstract: Our findings suggest that social capital may have an impact on children's well-being as early as the preschool years. In these years it seems to be the parents' social capital that confers benefits on their offspring, just as children benefit from their parents' financial and human capital. Social capital may be most crucial for families who have fewer financial and educational resources. Our findings suggest that those interested in the healthy development of children, particularly children most at risk for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
171
2
18

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(198 citation statements)
references
References 10 publications
4
171
2
18
Order By: Relevance
“…A school, as a social organisation whose members know, care about, trust and support one another, which has common goals and a sense of shared purpose (Battistich et al, 1995), provides the ideal situation to support the development of resilience in children. Strong associations have consistently been found between diminished social capital at the level of family and the school and children's academic attainment, completion of high school and increased behaviour problems (Marmot, 1998;Berkman et al, 2000;Putnam, 2000;Runyan et al, 1998;Cooper & Thornton, 1999). The research reported here supports the argument that the adoption of a health-promoting school approach builds 'organisational resilience' through increased levels of protective factors and a supportive environment.…”
Section: F F E E a A T T U U R R E Esupporting
confidence: 74%
“…A school, as a social organisation whose members know, care about, trust and support one another, which has common goals and a sense of shared purpose (Battistich et al, 1995), provides the ideal situation to support the development of resilience in children. Strong associations have consistently been found between diminished social capital at the level of family and the school and children's academic attainment, completion of high school and increased behaviour problems (Marmot, 1998;Berkman et al, 2000;Putnam, 2000;Runyan et al, 1998;Cooper & Thornton, 1999). The research reported here supports the argument that the adoption of a health-promoting school approach builds 'organisational resilience' through increased levels of protective factors and a supportive environment.…”
Section: F F E E a A T T U U R R E Esupporting
confidence: 74%
“…Another important contributor to rates of violence is social integration within the community [60]. Reduced social capital (which refers to the protective effects of social networks), manifesting in low social cohesion and interpersonal mistrust, has been linked with an increase in higher violence rates and economic inequality [61], and conversely, Earls [62] found a strong relationship between high levels of civic engagement and low levels of crime.…”
Section: Proximal Societal Factorsmentioning
confidence: 99%
“…Esta não pretende ser uma revisão completa, visto que novas evidências aparecem rapidamente. Com relação à saúde vários níveis de análise têm sido propostos: (i) indivíduos ou domicílios 53,54,55,56,57,58,59,60,61,62,63,64,65 ; (ii) vizinhança ou bairros 51,66,67,68,69,70,71 ; (iii) regiões 72,73 ; (iv) Estados de um único país 74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91 ; e (v) entre países 92,93 .…”
Section: Relacionamento Entre Capital Social E Saúdeunclassified
“…Níveis mais elevados de capital social também têm sido associados com reduzida delinqüência juvenil 63 , menores taxas de gravidez em adolescentes 46,81 , menor quantidade de problemas emocionais e comportamentais 54,57,61,62,66 , uso adequado de serviços de saúde 76,99 , menor experiência de problemas bucais 100,101, 102 entre outros 7,74,79 .…”
Section: Relacionamento Entre Capital Social E Saúdeunclassified